'She Made Herself up Provocatively for the Charming of the Eyes of Men' (Jdt. 10.4): Cosmetics and Body Adornment in the Stories of Judith and Susanna. (March 2019) - Quick, Laura
The use of cosmetics and body adornment in order to decorate and beautify oneself is an almost universal part of the human experience. This was also true of the ancient Palestinian culture that gave rise to the Hebrew Bible and early Jewish literature. Despite this, cosmetics and their function in the narratives in which they feature is an understudied subject within the academic scholarship of biblical literature. This article discusses the use of cosmetics in biblical and Jewish-Hellenistic texts, demonstrating that cosmetics were associated with immoral behavior and illicit sexual practices. Nevertheless, in the stories of Judith and Susanna, these characters apparently receive no such censure for applying cosmetic oil. By considering the use of cosmetics akin to a speech act, able to communicate something specific about one's social or sexual status, this article provides a new access to understanding these narratives and the characterisations of their female heroines.